Strategi Pemasaran Digital untuk Meningkatkan Kesadaran Merek pada CV Bintang Bangkit - Erry Donneli (Yayasan Literasi Sains Indonesia, 2026)
Digital marketing strategy is a series of systematically designed planning and marketing activities aimed at building, strengthening, and maintaining a company’s presence in the digital environment through the use of various online channels. The primary objective of implementing a digital marketing strategy is to increase brand awareness and attract new customers in a more effective and efficient manner. Through a well-planned digital marketing strategy, companies can achieve specific digital marketing objectives by selecting media and platforms that align with the characteristics of the target market. Enhancing brand awareness is a strategic investment for companies, as it plays a crucial role in creating competitive advantage, expanding market reach, building consumer trust, and fostering long-term customer loyalty. This study employs a literature review method to examine key concepts of digital marketing, including its definitions, types, and commonly used strategies. In addition, the article analyzes the impact of digital marketing strategies on brand awareness, discusses their implementation across various industries, and evaluates their effectiveness in increasing brand awareness, with a specific focus on CV Bintang Bangkit.